Development Strategy and Innovation of Non-Bank Islamic Financial Institutions: A Study on BMT, KSPPS, and Islamic Fintech in Indonesia - Sutandi; Anton Bawono (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
This study examines the development strategies and innovations of non-bank Islamic financial institutions (LKNBS) in Indonesia, focusing on Baitul Maal wa Tamwil (BMT), Sharia Cooperatives for Savings and Financing (KSPPS), and Islamic fintech. These institutions are crucial for promoting financial inclusion and supporting the Muslim community's economy, especially in underserved areas. However, they face challenges such as limited access to technology, low financial literacy, and competition from conventional financial institutions. The study applies Blue Ocean Strategy and Schumpeter's Innovation Model to address these challenges. Blue Ocean Strategy focuses on creating untapped market spaces and reducing competition by offering unique products and services, while Schumpeter's model emphasizes the importance of continuous innovation for driving growth and competitiveness. The study finds that non-bank Islamic financial institutions can leverage these strategies to develop innovative Sharia-compliant financial products and utilize digital platforms like mobile apps for microfinancing, digital payments, and crowdfunding. These innovations can enhance operational efficiency, broaden market access, and cater to underserved communities, particularly in rural areas and among micro, small, and medium enterprises (MSMEs). The study concludes with recommendations for adopting advanced technologies, supporting regulatory frameworks, and increasing market penetration to foster growth and sustainability. By adopting these strategies, LKNBS can strengthen their competitiveness and contribute to Indonesia’s economic development.